Identification of endophytic fungi in nutgrass (Cyperus rotundus L.) as solubilizing phosphate and indole-3-acetic acid producers - Nur Kusmiyati; Septian Tri Wicaksono; Durrotul Maknuna (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2021)
Low phosphate content in the soil causes insufficient plant needs. Meanwhile, endophytic fungi in nutgrass have great potential as a phosphate solvent and produce indole-3-acetic acid (IAA). Therefore, this study aims to determine the solubilizing phosphate and IAA production by the endophytic fungi of nutgrass and identify the isolates based on rDNA-ITS sequences. Endophytic fungi isolates were cultured in 10 ml of Pikovskaya broth media with Ca5(PO4)3 as the inorganic phosphate source. The PCR results were analyzed using 1.5% agarose gel electrophoresis followed by sequence analysis. The isolation and purification results showed five isolates coded URT1, URT2, URT3, URT4, and URT5, while the solubilizing phosphate levels ranged from 54.03-87.83 ppm, with the highest levels found in the URT4 isolate. Furthermore, the IAA levels ranged from 5.58-45.50 ppm, with the highest levels produced by the URT1 isolate. The molecular analysis with rDNA-ITS sequences showed that URT4 had 97.42% similarity to Aspergillus terreus species, while UTR1 had 100% similarity to Fusarium oxysporum species. Based on the results, the endophytic fungi of nutgrass from A. terreus and F. oxysporum species have great potential as biofertilizers due to the high solubilizing phosphate and IAA levels.